Use of PARP inhibitors in prostate cancer: from specific to broader application - Zhang, Zhenting; Diao, Lei; Zhang, Chao; Wang, Feifei; Guan, Xin; Yao, Xin (Frontiers in Endocrinology, 2023)
Prostate cancer (PC) is one of the major health issues of elderly men in the word. It is showed that there were approximately 1.414 million patients with PC in 2020 worldwide, with a high mortality rate in metastatic cases. In the present choices of treatment in PC, androgen deprivation therapy has long been as a backbone of them. But the clinical outcomes of patients with metastatic castration-resistant prostate cancer (mCRPC) were not ideal because of their poor prognosis, more effective therapeutic approaches are still necessary to further improve this problem. Poly (ADP-ribose) polymerase (PARP) inhibitors lead to the single-strand DNA breaks and/or double-strand DNA breaks, and result in synthetic lethality in cancer cells with impaired homologous recombination genes. It is estimated that approximately 20 25% of patients with mCRPC have a somatic or germinal DNA damage repair gene mutation. Furthermore, in “BRCAness” cases, which has been used to describe as tumors that have not arisen from a germline BRCA1 or BRCA2 mutation, there were also a number of studies sought to extend these promising results of PARP inhibitors. It is worth noting that an interaction between androgen receptor signaling and synthetic lethality with PARP inhibitors has been proposed. In this review, we discussed the mechanism of action and clinical research of PARP inhibitors, which may benefit population from “specific” to the “all-comer” in patients with PC when combined with novel hormonal therapies.